1 Public Records of the Colony of Connecticut 529-30 (J. Hammond Trumbull ed., 1850) (enacted 1650) - (:unkn) unknown (My University, 1642)
"It is Ordered that no man wthin this Jurisdictn shall, directly or indirectly, amend, repaire, or cause to be amended or repaired, any gun smale or greate, belonging to any Indean, nor shall indeavor the same, nor shall sell nor giue to any Indean, directly nor indirectly, any such gun, or any gunpowder or shott or lead or shott mould, or any millitary wepons, armor or arrowe heads, nor sell nor barter any such, vppon payne of ten pownd fyne for euery offence att lest, and the Court shall [have] power to [increase] the fine or to impose corporal( punishement where a fyne cannot be had, at their discretion."
Keywords: REQUIRED POSSESSION